Outsmart waste : the modern idea of garbage and how to think our way out of it - Szaky, Tom (Berrett-Koehler Publishers, Inc., 2014)
"Garbage doesn't exist in nature--the output of one organism is the useful input of another. So why does garbage exist in the human system? Why did it only become a problem the past century? And most importantly, how can we eliminate it--outsmart the very idea of garbage? Eco-entrepreneur Tom Szaky says that to outsmart waste first we have to understand it, then change how we create it, and finally rethink what we do with it. He traces the roots of our current garbage crisis to 20th century technological advances that resulted in historic changes in consuming habits--both the amount of garbage created and its longevity increased dramatically. Szaky argues we can turn this around by changing what we buy, when we buy, why we buy, and what we do with what we've bought. And through innovative recycling and creative "upcycling" (creating new products from discarded objects) we can stop seeing garbage as useless waste and start seeing it as useful waste--a tremendous volume of resources that are simply misunderstood. After reading this mind-expanding book you will never think of garbage the same way again"--